Diseño y construcción de equipo sencillo para la enseñanza de la física - Holguín Tabares, Carlos Arturo (Revista Científica, 2011)
Relevance as prototypes for the teaching of physics, there are different manufacturing companies, responsible for the dealing and supplying the market whit equipment to accompany and assist the theoretical development of the subjects whit the laboratories involved, wich applies to many educational institutions. In the process of training of human beings throughout their lives, no one questions the importance of experimentation and planning the construction of knowledge, whit gladness and pleasure, without the existence of laboratory equipment is necessary to design calculate and build simple equipment that satisfies these functions.